Possibilities and limitations of news values qualitative analysis: Application to sports journalism - Langer, Miroslav (Civilia, 2021)
'News values' is an established term for factors that determine the selection of topics and events into the news coverage. A primary method of the German tradition of news values research, the quantitative content analysis, requires construction of a robust codebook based on catalogs of news values. There are lists elaborated for general (political) news reporting, but their application to sports journalism carries the risk of distortion. The qualitative interviews conducted previously with editors of Czech sports media suggest how to modify the existing lists. This pilot research proves the legitimacy of these modifications, especially in the process of evaluation of positivity and negativity, ethnocentrism and status of the sport.
Keywords: News values; Sports journalism; Quantitative analysis